NEW METHODS FOR DETECTING BIOMARKERS OF OXIDATIVE STRESS AND REDOX SIGNALING ON PROTEIN CYSTEINE RESIDUES - Bechtold, Erika (Wake Forest University, 2010)
Both nitric oxide and hydrogen peroxide, as well as their respective metabolites (reactive nitrogen or oxygen species), participate in a variety of cellular redox processes and have become well recognized as messengers in cellular signal transduction. One important mechanism by which cellular redox-based signaling occurs is reversible oxidation of cysteine residues in the presence of low concentrations of these oxidants. S-Nitrosothiols (RSNO) and sulfenic acids (RSOH) are thought to be two of the most common cysteine modifications, and formation of these species reversibly alters protein function. Protein oxidation is studied to a lesser extent than lipid and DNA oxidation in part because of a lack of sensitive, stable, readily detectable markers for tracking these unstable intermediates.
Keywords: protein labeling; redox signaling; S-nitrosation; sulfenic acid